Current trends of HRM towards Effectiveness of the organisation - Rajamanthri , Dr. Senani (Archives of Business Research, 2021)
Human Resource Management (HRM) like many other fields in Business continues to rely largely on trends in the practices strategic objectives in maximising the performance of the employee while understanding them towards the effectiveness of the organisation. The HR Management Trends is the one which is concerned with focusing on the organizational design, system, HR and policies. It is essential that Human Resource Management is operating appropriately and in accordance with the latest trends impacted by ‘Covid19’ and technology to be able to deal with the business life challenges. In the study, current trends of HRM and their implications are identified and evaluated in understanding the present challenges towards better performing organisational activities following the design, system, HR and policies leading to the effectiveness of the company ensuring sustainable competitive advantage. Methodology utilizes the reviewing the current findings on studies coupled with a survey done with senior managers/HR managers of the corporate sector in the world with special reference to Australia. Hence, in addition to the literature review, this study was based on senior line managers and HR managers, and measures a range of subjective and objective outcomes. The analysis confirms the strong positive relationship between HR focused practices and HR effectiveness and it is proven that more the strong HR focused practices leads to higher range of performance outcomes. The associations are mostly stronger for HR effectiveness. There are low levels of agreement between HR and line managers about HR effectiveness and where agreement exists; it is not associated with superior outcomes. According to the study it is revealed that trends including personalisation of individual needs, work-life balance, Trusting issue of technology and leaders, Balancing three bottom-lines via proper managing HR towards CSR and sustainability, attitude towards Development, decreasing of the Employee Experience, withdrawn Paternalism, People Analytics, More expectation out of less effort (smart move), dealing with big innovative technology, HR is about People, HR Innovation Labs mainly resulted by the trends including handling the Covid19 context. This study, therefore, confirms the importance of HR effectiveness by well addressing these upcoming trends including handling the impact of Covid19 towards higher productivity and sustainable competitive advantage through proper managing most valuable live resource: people. It could be safely concluded that impact of coronavirus (Covid19) towards HRM as an accelerator for defining the role of the corporation, remote working, re-skilling, skills based hiring, and the transformation of corporate learning.